PENGEMBANGAN SISTEM INFORMASI MANAJEMEN PERIKANAN TANGKAP DALAM RANGKA PENGEMBANGAN INDUSTRIALISASI PERIKANAN LAUT (The Development of Capture Fisheries Management Information System in Relation to the Development of Marine Fisheries Industrialization) - John Haluan; Eko Sri Wiyono; Rikhie Supriyadi (Bogor Agricultural University, 2012)
ABSTRACTDeveloping capture fisheries management information system needs a Management Information System (MIS) which could support various aspects within an integrated and holistic system to gain better access of information on Marine Fisheries Industrialization in Indonesia. The objectives of the research are to investigate the management information system in lobster fisheries and develop management infomation system to support marine fisheries industrialization. This research implemented integrated approach information system for holistic system application. Applies a systems approach that takes into account the system as a whole integrated information for each activity or application. The system limits on the development of the lobster fishery in PPN Palabuhanratu. The technology used for processing the data and information on the lobster fishery is a computerized information technology. Analysis of system requirements derived from the fishing company, fishermen and stakeholders. Establishing the design of information systems in the lobster fisheries at PPN Palabuhanratu by identifying the real system, preparation of the scheme, providing menus, preparation of the logical flow of programs and computer applications. With the establishment of fisheries information management system will facilitate information services more quickly and accurately.Key words: capture fisheries, industrialization, management information system (MIS),——-ABSTRAKPengembangan sistem informasi manajemen perikanan tangkap dalam rangka pengembangan industrialisasi perikanan laut sudah mempunyai dasar hukum Undang-Undang Republik Indonesia No. 31 Tahun 2004 tentang Perikanan, tertera pada Bab VI: Sistem Informasi dan Statistik Perikanan, pasal 46: (1) â€œPemerintah menyusun dan mengembangkan sistem informasi dan data statistik perikanan serta menyelenggarakan pengumpulan, pengolahan, analisis, penyimpanan, penyajian, dan penyebaran data potensi, sarana dan prasarana, produksi, penanganan, pengolahan dan pemasaran ikan, serta data social ekonomi yang terkait dengan pelaksanaan pengelolaan sumberdaya ikan dan pengembangan sistem bisnis perikanan.â€ (2)â€Pemerintah mengadakan pusat data dan informasi perikanan untuk menyelenggarakan system informasi dan data statistic perikanan.â€; pasal 47: (1) â€œPemerintah membangun jaringan informasi perikanan dengan lembaga lain, baik di dalam maupun di luar negeri.â€, (2) â€œSistem informasi dan data statistic perikanan harus dapat diakses dengan mudah dan cepat oleh seluruh pengguna data statistic dan informasi perikanan.â€ Pengembangan sistem informasi manajemen perikanan tangkap perlu suatu Sistem Informasi Manajemen (SIM) yang dapat menunjang berbagai aspek dan elemen dalam suatu sistem yang holistik dan terintegrasi untuk mencapai tujuan meningkatkan akses informasi IPTEKS-Teknologi Tepat Guna (TTG) dalam Pelaksanaan Program Pengembangan Industrialisasi Perikanan Laut di Indonesia.Kata kunci: Perikanan tangkap, industrialisasi, sistem manajemen informasi